Long-Term Follow-Up of the Therapeutic Outcomes for Papillary Thyroid Carcinoma With Distant Metastasis. Issue 26 (July 2015) - Lin, Jen-Der; Hsueh, Chuen; Chao, Tzu-Chieh
Abstract : Abstract: Papillary thyroid carcinoma (PTC) patients with distant metastasis (DM) have variable clinical courses and therapeutic outcomes. Survival time after diagnosis of DM may be several months to years. Long-term follow-up is necessary to determine prognostic factors for survival in PTC with DM. The purpose of this study was to investigate the clinical features and therapeutic outcomes of PTC with DM after 10 years of follow-up. The study population consisted of 70 patients who underwent initial thyroidectomy before 2004 and had DM beyond the locoregional neck area. Of these 70 patients, 40 patients were diagnosed with DM before or within 9 months after initial thyroidectomy in first radioactive iodide ( 131 I) whole-body scintigraphy (group A), and 30 patients were diagnosed with DM during the follow-up period (group B). Patients with DM underwent 3.7 to 7.4 GBq 131 I therapy every 6 to 12 months. After a mean follow-up period of 10.1 ± 0.9 years, the disease-specific mortality and remission rates were 70.0% (49/70) and 10% (7/70), respectively. The survival rates for patients in groups A and B were 72.5% and 96.7% at 1 year, 47.5% and 90.0% at 5 years, 40.0% and 70.0% at 10 years, 36.4% and 41.1% at 15 years, and 35.0% and 8.0% at 20 years, respectively. The percentage of male and older patients and patients with larger tumor size was higher in the mortality group than in the survival group, whereas the percentage of patients with 131 I avid metastatic lesions (first DM) was lower in the mortality group. The percentage of patients with secondary primary cancers was higher in group B than in group A. In the multiple regression analysis, age and male gender were independently associated with disease-specific mortality. In conclusion, after a mean follow-up of 10.1 years, the disease-specific mortality rate for PTC with DM was 70.0%. Older patients and male PTC patients with DM need more aggressive treatment. The timing of DM diagnosis did not influence disease-specific mortality.